Development of magnetically separable MoS2/NiFe2O4 heterostructure for improved photocatalytic efficiency of malachite green (MG) degradation - Alanazi, Meznah M.; Abdelmohsen, Shaimaa A. M.; Alahmari, Saeed D.; Abdullah, Muhammad; Aman, Salma; Al-Sehemi, Abdullah G.; Farid, Hafiz Muhammad Tahir (Journal of materials science. Materials in electronics, 2024)
Photocatalysis is a multifaceted phenomenon that can be employed for diverse applications, such as waste management and the treatment of water resources. Through a hydrothermal process, a magnetic nanocomposite comprising MoS 2 and NiFe 2 O 4 with optical activity was effectively synthesized. The produced photocatalysts were subjected to different methods to investigate the physiochemical properties of the materials. The optical band-gap values of the fabricated nanocomposite were measured to be 1.75 and 1.57 eV accordingly for NiFe 2 O 4 and MoS 2 /NiFe 2 O 4 which were established by UV–Visible absorption spectrum via Tauc’s relation. From the BET study, the surface area of prepared MoS 2 /NiFe 2 O 4 NCs was achieved to be 71.05 m 2 g −1 . The photocatalytic efficacy was assessed by observing malachite green degradation in the existence of visible light conditions. The MoS 2 /NiFe 2 O 4 nanocomposite contains degradation efficiency of 98.28% in 140 min under visible source toward malachite green and demonstrated favorable reusability potential through magnetic separation. This finding indicates that the activity of synthesized nanocomposite is superior to that of isolated MoS 2 and NiFe 2 O 4 NPs. A plausible mechanism for photocatalysis was explicated with charge carriers and scavengers of free radicals. The primary contributors to dye degradation were responsible to be the OH radical and holes species.